Morphological and morphometric rearrangements of adenohypophysis structural components in rats under conditions of experimental extracellular dehydration of middle degree. - Hryntsova, N. B.; Romanіyk A. M.; Bumeister, V. I.; Karpenko, L. I.; Ustyansky, O. A.; Rudik, A. V. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. The constant composition of the water-electrolyte balance is a necessary condition for the vital activity of the organism. Violations of homeostasis cause significant changes in all systems of the body, including endocrine. Objective. The purpose of the work is to study the morphological and morphometric alterations of the vascular bed of adenohypophysis in sexually mature male rats under conditions of experimental secondary-depletion extracellular dehydration. Methods. The experiment was conducted on 12 white, sexually mature male rats weighing 250-300 g aged 7-8 months. The morphometric, statistical and generally accepted methods of microanatomical (histological) research were used. Morphological changes in the vascular bed are associated with the development of polycythemic hypovolemia and, as a consequence, hypoxia of the circulatory type. Results. Changes in the blood flow to the blood vessels (diffuse venous-capillary plethora), changes in the rheological properties of the blood (stasis with the initial stages of slimming and thrombotic formation), and the first signs of increased permeability of the vascular wall with the formation of single small-basal diaphragmatic microhemorrhages are revealed. Conclusion. The most pronounced morphological alterations of the vascular wall in the subcapsular zone of the gland. Adjustment of the vascular bed of adenohypophysis negatively affects the morphofunctional and secretory activity of endocrinocytes, the processes of evacuation of hormones in the vascular bed, the development of compensatory and adaptive processes in the body and the course of the general adaptation syndrome in response to the action of the damaging agent.